THE ROLE OF INTERCULTURAL COMPETENCE IN ENGLISH LANGUAGE TEACHING - Jovliyeva Nafosat Bahodir qizi (FANLARARO TAFAKKUR MAVZUSIDAGI ILMIY-AMALIY KONFERENSIYA, 2025)
Annotation: This article explores the importance of intercultural competence in English language teaching (ELT) and its role in preparing learners for effective communication in a globalized world. In addition to linguistic skills, successful communication requires awareness of cultural norms, values, and communicative conventions. The study examines how teachers can integrate intercultural elements into the English curriculum to enhance students’ understanding of cultural diversity and global citizenship. It also highlights strategies that promote tolerance, empathy, and mutual respect through language education. The findings emphasize that developing intercultural competence helps learners not only master English but also use it appropriately in multicultural contexts.